Errare humanum est – o kategorii „błędu” w średniowiecznych polskich manuskryptach. Prolegomena - Ziółkowska, Olga; Kuźmicki, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
Analysing the category of “error” in medieval Polish manuscripts, the authors of the article question the usability of contemporary definitions and typology of errors in the context of Old Polish source material. They argue that due to their specificity – multilingualism, the presence of Latin sources, genological multilayering and formulaic nature – it is difficult to determine clearly what is an error and what is a conscious stylistic device. The authors indicate that often an “error” is only an interpretation of the contemporary researcher rather than an objective phenomenon.